Associação genética entre características de crescimento de carcaça de tilápia do nilo (Oreochromis niloticus) - Garcia, André Luiz Seccatto (2016)
The aim of this study was to estimate genetic parameters for performance traits (daily weight gain, weight at biometry and weight at slaughter), weight and fillet yield and fat percentage in the fillet of Nile tilapia strain Aquaamerica. Animals from the third generation of Aquaamerica strain were used and for performance traits. The data contained information of 2585 animals, males and females, and for fat percentage, weight at slaughter, weight and fillet yield only males were evaluated, with 1136, 1204, 1198 and 1198 animals respectively. Different models were tested for each trait and the best model was selected based on the Deviance Information Criterion (DIC). Analyses were performed using the software GIBBS1F90 (BLUPF90 family of programs). For the estimation of variance components, heritability and common environmental effect were performed univariate analyzes using animal model. Heritability estimates were moderated and ranged between 0.2 (fat) to 0.41 (slaughter weight). For the estimation of (co)variance components and calculation of genetic and phenotypic correlations, bivariate analyzes were performed considering daily weight gain with fat and fillet yield; final weight with fat and fillet yield; and fillet yield and fat. Only the genetic correlation between fillet yield and fat was significant (0.6), thus no correlated responses are expected in fillet yield when using performance traits as selection criteria. On the other hand the genetic correlation between fat and fillet yield points to the possibility of correlated response to selection therefore, if using fillet yield as selection criteria, the expected correlated response on fat percentage would be 7.81% in the next generation.